Using a Collaborative Assessment Design to Support Student Learning - Shannon Kennedy-Clark; Sean Kearney; Vilma Galstaun (Education Sciences, 2017)
The purpose of the study was to try to develop an understanding of how groups of pre-service teachers organised, planned and built two information and communication technologies (ICT) resources using a learn-technology-by-design framework. The benefits for students in using a learn-by-design approach have been well researched, and the research has covered a broad range of research streams. A design-based research approach underpins the research. This paper presents the observational data, which was collected in an ICT in the Education unit of study. The collaborative design assessment provided pre-service teachers with the opportunity to collaboratively build an Interactive Whiteboard (IWB) resources and a web-based teaching (website) resource. In this study, seven groups were observed while they engaged in a long-term collaboration and completed two group assessment tasks. The results suggest that students needed both guidance and time to develop their skills in collaboration. While there were variations in the collaborative patterns, these variations did not impact the success of the groups in the development of their ICT resources.